Analisis Komparasi Sistem Pendidikan Indonesia dan Finlandia - Sundari Sundari; Komarudin Sassi (CV. Alim's Publishing, 2024)
Education currently occupies a very important position in human development. The quality of the Finnish educational system is interesting to study because its success has been recognized worldwide. This study provides an overview of the comparison of the education systems of the countries of Indonesia and Finnish. The method used in this study is literature study. The results of the study show several differences, (1) Indonesia's educational system is colored by many competitions while Finnish puts forward the principle of equality; (2) Indonesia has a system of failing a grade and student ranking, Finnish has’nt failing a grade and ranking system; (3) Indonesia load learning every week +/- 40 hours, Finnish lessons +/- 30 hours per week; (4) Indonesia learns a lot in class, Finnish puts forward problem solving methods; (5) Indonesia assignments almost become a routine agenda every face to face, Finnish does not burden students with a lot of tasks, (6) Indonesia minimum teacher qualifications D4, Finnish minimum teacher qualifications S2 (Master), (7) Indonesian qualifications students enter basic education for at least 6 years (5.5 years accompanied by written recommendations from professional psychologists), Finnish qualifications for students entering basic education for at least 7 years.